Comparison of predator prey interaction models for fish assemblages from the neotropical region - PIANA, P.A.; GOMES, L.C.; AGOSTINHO, A.A. (2018)
PIANA, Pitágoras Augusto; GOMES, Luiz Carlos; AGOSTINHO, Angelo Antonio. Comparison of predator prey interaction models for fish assemblages from the neotropical region. Ecological Modelling, Amsterdam, v.192, no.1-2, p.259-270, 2006.